Learning Goal Orientation (LGO) and Mentor Function Effect on Entrepeneurship Self-Efficacy in Medium Small Enterprises Bojonegoro - Eriani, Izmi Dwira; Nurul, Mochammad; Rosyidiana, Riska Nur; Chen, Yanning (TIJAB (The International Journal of Applied Business), 2023)
Background: The role of an entrepreneur's internal dispositions and external support mechanisms in influencing self-efficacy remains a subject of keen interest. The Bojonegoro region, with its unique entrepreneurial landscape, provides a rich context for such exploration. Objective: To unravel the intricate relationships which shape an entrepreneur's self-efficacy, focusing primarily on the contributions of Learning Goal Orientation (LGO) and Mentoring Function (MF). Method: A questionnaire-based approach was employed targeting 30 small and medium-sized enterprises (SMEs) in Bojonegoro, using the purposive sampling method. The gathered data was meticulously analyzed using SPSS's 25th edition under multiple linear regression analysis. Results: Findings highlighted the significant positive effect of LGO on Entrepreneur Self-Efficacy. While MF alone did not directly influence self-efficacy, its combined effect with LGO showcased a synergistic positive impact. Conclusion: The research underscores the importance of both an entrepreneur's learning mindset and effective mentoring in shaping self-efficacy. Emphasizing these factors can offer a  more holistic approach to entrepreneurial training and development programs, especially in regions akin to Bojonegoro. Keywords: Entrepreneur Self-Efficacy, Learning Goal Orientation (LGO), Mentoring Function (MF), Small and Medium-sized Enterprises (SMEs)